Urban–rural differences in related factors of second-hand smoke exposure: a cross-sectional study of adult non-smokers in Northeast China. (24th July 2018) - Gao, Chunshi; Yao, Yan; Niu, Huikun; Li, Lu; Li, Meiqi; Qu, Yangming; Wang, Rui; Zhang, Peng; Li, Meng; Yan, Shoumeng; Li, Bo
Abstract: Background: this study aims to examine the different factors associated with exposure to second-hand smoke (SHS) between urban and rural areas and to facilitate a reduction in SHS exposure in Northeast China. Methods: a multistage stratified random cluster sampling design was used in this 2012 cross-sectional survey in Jilin Province, Northeast China. A total of 13 056 non-smokers were included in this study. The Rao–Scott χ 2 test, multiple regression analysis and discriminant function analysis were used. Results: the SHS prevalence among adult non-smokers was 60.2% in urban areas and 61.8% in rural areas. In urban areas, males were more likely to be exposed to SHS, while in rural areas, females were more likely to be exposed to SHS ( P < 0.05). Increasing age was a protective factor against SHS exposure both in urban and rural areas ( P < 0.05). Tobacco-relevant knowledge was positively associated with SHS exposure. Among urban non-smokers, high education level and engagement in manual work were risk factors for SHS exposure, and retired subjects were less likely to be exposed to SHS ( P < 0.01). Conclusions: non-smokers from urban and rural areas differ in the factors associated with SHS exposure, and urban–rural differentials, especially with regard to gender, should be considered in tobacco control.